Aplikasi Pembelajaran Digital: Implementasi Pembelajaran Inkuiri untuk Miningkatkan Kemampuan Membaca Pemahaman - Surya Sagiro Batubara; Basikin . (Institut Pendidikan Tapanuli Selatan, 2020)
This classroom action reserach aims to investigate the effectiveness of digital learning by implementing an inquire-based instruction approach in teaching to write a narrative text in Kelas IX-B in SMP Negeri 15 Cirebon. This research did in two teaching cycles, and the participants of this study were the researcher herself as a participant-observer and 28 students. This is a qualitative study for this study investigated the value of teaching writing by using technology digital as teaching madia and learning sources, and the finding from the classroom observation and the students’ texts were analyzed and then described according to the genre’s theorists. This study finds that the stage on an Inquiry-Based Instruction Approach is significant to improve students’ ability in many aspects in English writing. The elaboration supported students’ knowledge in vocabulary, grammar, and text features. However, teacher who intends to implement the Inquiry-Based Instruction Approach needs to have a sufficient knowledge regarding the approach, in order to be able to implement the approach better. Since the teaching program with sufficient time and broaden cycle might contribute on more significant finding regarding the primary issue.